58 Effect of Varespladib-Protected Surfactant in Cultured Rat Alveolar Macrophages Stimulated with LPS. (October 2012) - Luca, D De; Vendittelli, F; Fraser, H; Gentile, L; Trias, J; Minucci, A; Capoluongo, ED
Abstract : Background: Secretory phospholipase A2 (sPLA2) is a crucial enzyme for inflammatory response and surfactant catabolism. Acute lung injury (ALI) is a life-threating syndrome characterized by surfactant dysfunction and raised levels of sPLA2. Varespladib is a potent selective sPLA2 inhibitor that is effective in animal models of ALI. Nothing is known about the joint administration surfactant+varespladib and we aimed at studying the effect on the sPLA2 pathway. Methods: 1x10 6 normal alveolar macrophages (from Rattus Norvegicus ) were cultured in Ham'sF12 medium + 2% fetal bovine serum. Cultures were incubated with 15 ng/mL LPS for 24h, then treated with 200 µg poractant-α, 90 µM varespladib, both or nothing. These concentrations were those achieving 50% sPLA2 activity reduction in previous experiments. After 24h, culture supernatants were assayed for sPLA2 activity, free fatty acids (FFA) and total proteins concentrations. Results: sPLA2 activity corrected for the protein level is 0.26±0.02, 0.24±0.02, 0.24±0.02 and 0.28±0.02 IU/µg in cultures treated with surfactant, varespladib, both or nothing (overall p =0.016; Dunnett post-hoc between cultures treated with varespladib and varespladib+surfactant against untreated cultures p =0.01). FFA are higher in untreated cultures (394±82 µM), than in surfactant- (219±70 µM) and in varespladib-treated ones (148±51 µM). Combined treatment reduced FFA to 206±47 µM (overall p=0.017; Sidak post-hoc p =0.036 and p =0.023 for the varespladib and combined treatment against control cultures). Conclusions: The joined administration of varespladib and poractant-α significantly reduce sPLA2 activity and FFA production. Surfactant+varespladib affect sPLA2 pathway significantly more than the surfactant alone.